Evaluación de la viabilidad para la implementación de plantas desalinizadoras usando energías renovables en la región de la Guajira Colombiana (2019)
This script is focused on the evaluation of the viability of implement a desalination plant in the region of Colombian Guajira driven by renewable energy; starting with a search for information about each one of the renewable energy and those that have been implemented in Colombia, afterwards each of the desalination processes and the possible combinations of these with renewable energies are evaluated. Finally the information about the geographic, social and economic conditions of the region is search, besides the access to drinking water that the inhabitants have, in order to choose the desalination system and energy that better fits to the conditions of the Guajira region. According to the research the wind power and photovoltaic solar energy, both are very promising thanks to the weather and climate conditions in Guajira, but with the bibliographic revision is recommended the use of photovoltaic solar energy with the reverse osmosis system that has low energy consumption.